Drivers of primary care appointment volumes before and after the COVID-19 pandemic: a longitudinal study - Tianchang Zhao; Rachel Meacock; Matt Sutton (BMC Health Services Research)
Abstract Background The COVID-19 pandemic led to significant reconfiguration of primary care systems internationally. For example, a large proportion of face-to-face appointments have been replaced by telephone or online consultations. As a result, the relationship between primary care appointment provision and some of its key determinants, such as workforce and demographic characteristics, are likely to have changed. Conclusions from previous studies which used only pre-pandemic data may no longer be applicable under these new configurations. Methods This study aims to investigate whether the relationships between primary care appointment rates and their determinants, including workforce composition and the age structure of registered patients, have changed after the COVID-19 pandemic. We conducted longitudinal analysis on the 106 Clinical Commissioning Groups (CCGs) in England over two periods of 24 months (March 2018 to February 2020 and March 2021 to February 2023). We used fixed-effects regression models to relate monthly general practice appointment rates per registered patient to workforce size and composition and population age structure, and compared the results between the two periods. Results In the pre-pandemic period, changes in full time equivalent (FTE) numbers of GP trainees and nurses were the only time-varying variables associated with appointment rates. In the post-lockdown period, the age profile of registered patients became a key determinant of appointment rates. A 1% increase in the proportion of registered patients over 80 years was associated with a 0.165 (38.7%) increase in appointments per patient per month. Changes in FTE numbers of qualified GPs and direct patient care staff were not found to influence the appointment rate in either period. Conclusion The relationships between primary care appointment rates and the workforce composition and population age structure have changed following the COVID-19 pandemic. The proportion of registered patients over the age of 80 years is now the most significant time-varying driver of appointment rates. General practices serving older patients may face much higher demand and have a bigger challenge providing sufficient appointments in the future compared to before the pandemic.